THE ROLE OF PATAN MUSEUM IN PRESERVING NEWAR CULTURAL HERITAGE - Nyaupane, Pashupati (International Journal of Research -GRANTHAALAYAH, 2025)
The Patan Museum is integral to preserving the Newar people’s rich cultural heritage in the Kathmandu Valley. The museum is a significant institution dedicated to conserving the historical, architectural, and cultural legacy of Nepal’s indigenous Newar people. It is located in the heart of Patan Durbar Square, among a collection of medieval palaces. The rich traditions of the Newar people are represented by the numerous sacred sculptures, paintings, metalwork, and architectural elements in the museum’s collection that date back to the Middle Ages. In addition to serving as a repository for these cultural treasures, the museum offers an educational platform that bridges the past and present. The museum encourages a deeper understanding of the traditions of the community, which are deeply rooted in the tangible and intangible elements of their cultural identity, by presenting the many parts of Newar life, including religion, crafts, and festivals. Furthermore, the Patan Museum is essential in protecting Newar culture from risks posed by urbanization, modernization, and natural disasters. Through collaborations with local communities, governmental bodies, and international organizations, the museum has evolved into an organizer for heritage conservation initiatives that ensure that Newar traditional practices remain in a world that is continuously changing.